Jumping from the highest graded readers to ungraded novels: four case studies - Uden, Jez; Schmitt, Diane; Schmitt, Norbert (University of Hawaii, 2014)
This study follows a small group of learners in the UK to the end of a graded reading program using the Cambridge Readers and investigates whether this particular graded reading series provides a bridge to reading unsimplified novels for pleasure. The participants’ reading comprehension, reading rates, vocabulary text coverage, and overall affect were measured and used for comparison between two of the highest level Cambridge Readers and two ungraded novels. The four books were also analysed to investigate the potential ‘gap’ in vocabulary coverage between graded and ungraded fiction. The overall results revealed that learners can progress from a graded reading program using the Cambridge Readers to reading unsimplified novels for pleasure, but are likely to experience a reduction in vocabulary coverage from over 98% to around 95%. It was also found that the gap between graded and unsimplified novels may not be as big as previously thought.